2023
DOI: 10.3389/fpsyt.2022.1067260
|View full text |Cite
|
Sign up to set email alerts
|

Frailty among inpatients with Schizophrenia: Status, influencing factors, and their correlation with quality of life

Abstract: ObjectiveThis study aimed to understand frailty and its influencing factors in inpatients with Schizophrenia in Chengdu and to explore correlations between frailty and quality of life.MethodsFrom May to July 2022, inpatients with Schizophrenia were surveyed using a general information questionnaire, frailty phenotype (FP) scoring, the Self-Rating Depression Scale (SDS), the Mini-Mental State Examination (MMSE), and the SZ Quality of Life Scale (SQLS). Multivariate logistic regression was conducted to assess fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Notably, several studies have indicated a high prevalence of frailty among individuals diagnosed with schizophrenia, including those in younger age groups (39,40). Recent studies also have demonstrated strikingly similar patterns of gene activity in aging and schizophrenic patients, particularly in neurons and astrocytes in the prefrontal cortex (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, several studies have indicated a high prevalence of frailty among individuals diagnosed with schizophrenia, including those in younger age groups (39,40). Recent studies also have demonstrated strikingly similar patterns of gene activity in aging and schizophrenic patients, particularly in neurons and astrocytes in the prefrontal cortex (41).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that pre-existing frailty in older adults was correlated with increased likelihood of enduring and abrupt MI during the initial wave of the COVID-19 pandemic, and this association persisted ( 37 , 38 ). Notably, several studies have indicated a high prevalence of frailty among individuals diagnosed with schizophrenia, including those in younger age groups ( 39 , 40 ). Recent studies also have demonstrated strikingly similar patterns of gene activity in aging and schizophrenic patients, particularly in neurons and astrocytes in the prefrontal cortex ( 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Structural abnormalities of the cortex are associated with several diseases and conditions 16 19 . Neuropsychiatric diseases cause structural changes in the brain; schizophrenia and Parkinson’s disease are associated with frailty 20 , 21 . There have been scattered reports that exercise can improve cortical thinning in patients with schizophrenia 22 and that cortical thickness can predict motor responsiveness in patients with Parkinson's 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Addressing factors that contribute to frailty, with a comprehensive and multidimensional approach that considers not only the control of the symptoms but also the physical, psychological, social, and functional factors, is a necessary intervention aimed at achieving full recovery. Further research is needed to explore the biological, psychological, and sociocultural mechanisms underlying the relationship between SMI and frailty, to analyze and prevent the clinical implications of frailty across different psychiatric disorders, including schizophrenia [404], bipolar disorder, and major depressive disorder, and to develop personalized and appropriate interventions to improve quality of life and delay the onset of frailty for this vulnerable population [405].…”
Section: Frailty and Deliriummentioning
confidence: 99%